(untitled) (Economic and Political Thought, 2015)
The period 2002–2005 was a specific time for the Polish foreign policy. On the one hand, our future membership in the European Union was being clarified and, on the other hand, the involvement of Poland in the conflicts in Iraq and Afghanistan was growing. The article is an attempt to analyse the international position of Poland in the period and its influence of our foreign policy. One of the aims is to verify the thesis that the period 2002–2005 was the end of a consensus on Poland’s foreign policy reached by the main political powers in Poland. The article deals with the following issues: the end of accession negotiations, the first year of membership, the role of Poland in transatlantic relations and the policy of the authorities towards East European states.